Calculus-Based Physics II - Schnick, Jeffrey; Open Textbook Library (Open Textbook Library, 2008)
Calculus-Based Physics is an introductory physics textbook designed for use in the two-semester introductory physics course typically taken by science and engineering students.
1 Charge & Coulomb's Law -- 2 The Electric Field: Description and Effect -- 3 The Electric Field Due to one or more Point Charges -- 4 Conductors and the Electric Field -- 5 Work Done by the Electric Field, and, the Electric Potential -- 6 The Electric Potential Due to One or More Point Charges -- 7 Equipotential Surfaces, Conductors, and Voltage -- 8 Capacitors, Dielectrics, and Energy in Capacitors -- 9 Electric Current, EMF, Ohm's Law -- 10 Resistors in Series and Parallel; Measuring I & V -- 11 Resistivity, Power -- 12 Kirchhoff's Rules, Terminal Voltage -- 13 RC Circuits -- 14 Capacitors in Series & Parallel -- 15 Magnetic Field Intro: Effects -- 16 Magnetic Field: More Effects -- 17 Magnetic Field: Causes -- 18 Faraday's Law, Lenz's Law -- 19 Induction, Transformers, and Generators -- 20 Faraday's Law and Maxwell's Extension to Ampere's Law -- 21 The Nature of Electromagnetic Waves -- 22 Huygens's Principle and 2-Slit Interference -- 23 Single-Slit Diffraction -- 24 Thin Film Interference -- 25 Polarization -- 26 Geometric Optics, Reflection -- 27 Refraction, Dispersion, Internal Reflection -- 28 Thin Lenses: Ray Tracing -- 29 Thin Lenses: Lens Equation, Optical Power -- 30 The Electric Field Due to a Continuous Distribution of Charge on a Line -- 31 The Electric Potential due to a Continuous Charge Distribution -- 32 Calculating the Electric Field from the Electric Potential -- 33 Gauss's Law -- 34 Gauss's Law Example -- 35 Gauss's Law for the Magnetic Field, and, Ampere's Law Revisited -- 36 The Biot-Savart Law -- 37 Maxwell's Equations
In English.
Description based on online resource
Keywords: Science -- Textbooks; Physics -- Textbooks